2012
DOI: 10.1136/oemed-2012-100845
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma risk and occupational exposure to pesticides: results of the Epilymph study

Abstract: Objectives Several agricultural pesticides have shown a carcinogenic potential in experimental animals. Methods In 1998-2003, 2337 incident lymphoma cases and 2434 controls participated in the EPILYMPH case-control study in six European countries. A detailed occupational history was collected in cases and controls. Specifi c questions for farm workers included type of crop, farm size, pests being treated, type and schedule of pesticide use. We conducted a preliminary analysis of risk of lymphoma and its major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 83 publications
1
89
3
2
Order By: Relevance
“…First, glyphosate risk estimates in several studies were based on small numbers of events in the exposure subcategories considered. For example, the case-control studies of NHL reported by Hardell et al (2002), Cocco et al (2013), and Eriksson et al (2008) and of MM reported by Orsi et al (2009) involved less than 10 exposed cases and/or controls overall or in specific glyphosate exposure categories. Even the large cohort study of 57 311 pesticide applicators conducted by De Roos et al (2005) and reanalyzed by Sorahan (2015) included sparse data (viz., 10 or fewer glyphosateexposed MM cases in each of the three exposure categories considered).…”
Section: Statistical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, glyphosate risk estimates in several studies were based on small numbers of events in the exposure subcategories considered. For example, the case-control studies of NHL reported by Hardell et al (2002), Cocco et al (2013), and Eriksson et al (2008) and of MM reported by Orsi et al (2009) involved less than 10 exposed cases and/or controls overall or in specific glyphosate exposure categories. Even the large cohort study of 57 311 pesticide applicators conducted by De Roos et al (2005) and reanalyzed by Sorahan (2015) included sparse data (viz., 10 or fewer glyphosateexposed MM cases in each of the three exposure categories considered).…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…Scanning the ensemble of hundreds of effect estimates shows that the vast majority of estimates (though not for glyphosate) were greater than one, suggesting systematic error across the various analyses. Cocco et al (2013) reported results from the EPILYMPH case control study of NHL in six European countries, conducted in 1998-2004. The study included 2348 incident lymphoma cases and 2462 controls.…”
Section: Nhl Studiesmentioning
confidence: 99%
“…An increased risk of CLL is consistently observed among those with family history of haematological malignancies. Other suspected risk factors include long-term use of pesticides and regular use of hair dyes (Benavente et al, 2005;Cocco et al, 2013;Montserrat & Moreno, 2008;Slager et al, 2014). However, its aetiology remains unknown and infections have been suggested as potential candidates.…”
Section: Received 9 January 2015mentioning
confidence: 99%
“…Improper use and disposal of containers of pesticide are mainly caused by inadequate knowledge, inadequate equipment, and storage, application of unregistered and nonapproved pesticides, and the use of an excessive dosage [2]. The exposure of farmers to agrochemicals has short term and long term effects [8,9].…”
Section: Advances In Agriculturementioning
confidence: 99%